2011
DOI: 10.1016/j.nlm.2011.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Examining the sex- and circadian dependency of a learning phenotype in mice with glycine transporter 1 deletion in two Pavlovian conditioning paradigms

Abstract: Behavioural characterisation of transgenic mice has been instrumental in search of therapeutic targets for the modulation of cognitive function. However, little effort has been devoted to phenotypic characterisation across environmental conditions and genomic differences such as sex and strain, which is essential to translational research. The present study is an effort in this direction. It scrutinised the stability and robustness of the phenotype of enhanced Pavlovian conditioning reported in mice with foreb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Female subjects display a faster acquisition rate and elevated responding during drug self-administration (Lynch and Carroll, 1999;George et al, 2021). Females exhibit higher levels of conditioned freezing relative to males during fear conditioning (Dubroqua et al, 2011). Sex differences have also been identified in Pavlovian conditioning tasks employing food rewards (Stringfield et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Female subjects display a faster acquisition rate and elevated responding during drug self-administration (Lynch and Carroll, 1999;George et al, 2021). Females exhibit higher levels of conditioned freezing relative to males during fear conditioning (Dubroqua et al, 2011). Sex differences have also been identified in Pavlovian conditioning tasks employing food rewards (Stringfield et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned research was primarily performed in male subjects, however increasing evidence highlights sex differences in dopamine neuron activity and release (Xiao and Becker, 1994;Walker et al, 2000;McArthur et al, 2007;Becker and Chartoff, 2019;Brundage et al, 2021;Zachry et al, 2021). These differences in dopamine transmission between males and females could account for the observed sex differences in dopamine-dependent behaviors (Lynch and Carroll, 1999;Dubroqua et al, 2011;Eubig et al, 2014;Pitchers et al, 2015;Stringfield et al, 2019;Zachry et al, 2019;Kutlu et al, 2020;Chen et al, 2021;George et al, 2021). While certain forms of Pavlovian conditioned responding can differ between males and females (Stringfield et al, 2019), it is not known if sex differences during Pavlovian learning is accompanied by distinct patterns of dopamine signaling.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned research was primarily performed in male subjects; however, increasing evidence highlights sex differences in behavioral responding. Across studies, female subjects display augmented behavioral responses compared with males, including higher locomotor activity, faster latency, and elevated conditioned responding ( Lynch and Carroll, 1999 ; Dubroqua et al, 2011 ; Eubig et al, 2014 ; Scholl et al, 2019 ; Stringfield et al, 2019 ; Zachry et al, 2019 ; Kutlu et al, 2020 ; Bishnoi et al, 2021 ; Chen et al, 2021 ; George et al, 2021 ; Knight et al, 2021 ). Furthermore, prior research has identified sex differences in dopamine neuron activity and release ( Xiao and Becker, 1994 ; Walker et al, 2000 ; McArthur et al, 2007 ; Becker and Chartoff, 2019 ; Brundage et al, 2021 ; Zachry et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sex differences also occurred for the behavioral effects of genetic deletion of forebrain GlyT-1. During extinction of appetitive Pavlovian conditioning (nose pokes during conditioned stimulus presentations in absence of reward), male mice with genetic deletion of GlyT-1 exhibited facilitated extinction compared to male control mice, whereas female mice with genetic deletion of GlyT-1 exhibited resistance to extinction compared to female control mice [81]. In terms of the NMDA receptor, female rats were shown to have higher levels of the NR2B subunit (glutamate binding site) in the hippocampus and higher levels of the NR1 subunit (glycine binding site) in the hippocampus, prefrontal cortex, and amygdala compared to male rats [82].…”
Section: Ee + Org24598 Failed To Inhibit Reacquisition Of Cocaine Self-administration In Female Rats: Sex Differencesmentioning
confidence: 99%